2000
DOI: 10.1111/j.0435-3676.2000.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

The verification and significance of three approaches to longitudinal stresses in high–resolution models of glacier flow

Abstract: Hubbard, A., 2000: The verification and significance of three approaches to longitudinal stresses in high-resolution models of glacier flow. Geogr. Ann., 82 A (4): 471-487.ABSTRACT. With the purpose of improving the ice physics underpinning time-dependent glacier flowline models, three independent approaches for solving longitudinal stresses in glaciers are discussed and verified by application to Haut Glacier d'Arolla. To highlight any shortcomings, the reduced and much utilised driving stress approximation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Our equations fall into type L1L2 of Hindmarsh's (2004) categorization of various approximate schemes, which is found to yield relatively accurate results. Using a similar technique to ours, Hubbard (2000) found that results for a valley glacier agree well with those using a higherorder model. Hindmarsh (1993Hindmarsh ( , 1996 and Hindmarsh and Le Meur (2001) have investigated whether the dynamics of the narrow transitional region near the grounding line matter for overall equilibrium and stability properties, but these issues remain unresolved.…”
Section: Combined Ice Sheet-shelf Modelsupporting
confidence: 74%
“…Our equations fall into type L1L2 of Hindmarsh's (2004) categorization of various approximate schemes, which is found to yield relatively accurate results. Using a similar technique to ours, Hubbard (2000) found that results for a valley glacier agree well with those using a higherorder model. Hindmarsh (1993Hindmarsh ( , 1996 and Hindmarsh and Le Meur (2001) have investigated whether the dynamics of the narrow transitional region near the grounding line matter for overall equilibrium and stability properties, but these issues remain unresolved.…”
Section: Combined Ice Sheet-shelf Modelsupporting
confidence: 74%
“…Ice flow occurs through internal deformation and Weertman (1964)-type sliding when basal temperatures reach the pressure melting point, and which is adjusted with a dimensionless scaling factor. Longitudinal stresses become increasingly important in high resolution models such as the one used here, and are computed using an empirically validated ice-stretching algorithm (Hubbard, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The mass balance model was constructed and tested using mass balance and climate data from the period 2000-2005 and it is not possible to distinguish between these two possibilities.…”
Section: Past Responsementioning
confidence: 99%